Predictors of Nurses’ Readiness in Code Blue Events: A Quantitative Analysis - Apriani, Nuni; Sanusi, Santy; Rismawati, Nita (Jurnal Pendidikan Keperawatan Indonesia, 2025)
Introduction: intra-hospital cardiac arrest (IHCA) is a life-threatening event requiring rapid and coordinated responses through a hospital emergency system known as code blue. Nurses are often the first responders, and their readiness directly affects patients’ survival outcomes. Multiple organizational, psychological, training, and practical skill factors may influence this readiness. Objective: this study aimed to examine the factors influencing nurses’ readiness in responding to code blue calls, focusing on organizational support, psychological conditions, training and simulation, and practical skills. Methods: quantitative analytic-descriptive design was applied among nurses assigned to the code blue team. Data were collected using structured questionnaire and analyzed with logistic regression to determine the relationship between independent variables and nurse readiness. Result: The logistic regression model showed strong explanatory power (R=0,881; R2=0,776) indicating that 77,6% of variance in readiness could be explained by the independent variables. Organizational factors had a statistically significant associated with readiness